2015
DOI: 10.1016/j.ejso.2015.03.224
|View full text |Cite
|
Sign up to set email alerts
|

Whole mount microscopic sections reveal that Denonvilliers' fascia is one entity and adherent to the mesorectal fascia; implications for the anterior plane in total mesorectal excision?

Abstract: ReuseUnless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or other rights-holder may allow further reproduction and re-use of this version -refer to the White Rose Research Online record for this item. Where records identify the publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 37 publications
5
25
0
Order By: Relevance
“…The architecture of the levator and sphincter ani complexes, the urethral sphincter, and the perineal body and its extensions have been topics of contention for over a century and still attract attention (Dickinson, 1889;Oelrich, 1983;DeLancey, 1986;Woodman & Graney, 2002;Kearney et al 2004;Yucel & Baskin, 2004;Wallner et al 2009), implying that their anatomy is still incompletely understood. The connections of these entities with neighboring structures in particular remain topics of contention (Uhlenhuth & Day, 1948;Milley & Nichols, 1969;DeLancey & Starr, 1990;DeLancey, 1992;Fritsch et al 2004;Kraima et al 2015). These disagreements probably originate in the deep position and, hence, limited accessibility of the pelvic floor within the bony pelvis.…”
Section: Introductionmentioning
confidence: 99%
“…The architecture of the levator and sphincter ani complexes, the urethral sphincter, and the perineal body and its extensions have been topics of contention for over a century and still attract attention (Dickinson, 1889;Oelrich, 1983;DeLancey, 1986;Woodman & Graney, 2002;Kearney et al 2004;Yucel & Baskin, 2004;Wallner et al 2009), implying that their anatomy is still incompletely understood. The connections of these entities with neighboring structures in particular remain topics of contention (Uhlenhuth & Day, 1948;Milley & Nichols, 1969;DeLancey & Starr, 1990;DeLancey, 1992;Fritsch et al 2004;Kraima et al 2015). These disagreements probably originate in the deep position and, hence, limited accessibility of the pelvic floor within the bony pelvis.…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that TME should be carried out in front of the fascia to ensure radical resection particularly in anterior rectal tumours [6]. Also, this part of TME is particularly difficult due to limited access created by pelvic angles and the prostate anteriorly in men.…”
mentioning
confidence: 99%
“…In agreement, pelvic surgeons occasionally report peritoneal troughs that extend to the pelvic floor in neonates (Uhlenhuth et al 1948) or coelomic remnants on the pelvic floor in adults (Heald & Moran, 1998). The fascia as such develops only after birth (Kraima et al 2015).…”
Section: Fate Of the Peritoneal Troughmentioning
confidence: 87%